Exercise Counseling by Primary Care Physicians in Jordan-A Preliminary Study - Othman Beni Yonis; Rami Saadeh; Zaher Chamseddin; Hussam Alananzeh (SAGE Publishing, 2020)
Despite the value of physical activity and exercise to patients, little is known about the perception and practices of Jordanian primary care physicians (PCPs) regarding counseling patients about exercise. This study was aimed at assessing counseling about exercise by PCPs in Jordan. A cross-sectional study targeting a random sample of physicians from family medicine, internal medicine and general practice in academic, public, and private sectors. Chi-square test of independence was used to assess the association of perceptions and practices of physicians regarding exercise counseling with their specialty. Logistic regression models were used to examine the association of demographic information with selected items of perception and practice. A total of 218 physicians participated in the study. They were mainly males (67%), family medicine physicians (42.2%), and had a mean age of 33.7 (±9.87) years. Most physicians believed that less than half of patients will start exercising (91.3%) or will continue exercising if they were repeatedly counseled at follow-up visits (85.4%). Family medicine physicians counseled more patients, more frequently, and their desire to counsel more patients was significantly higher than other physicians ( P  = .002). The Perceptions and practices of Jordanian PCPs toward exercise counseling for their patients were found positive; however the desire to counsel more patients was low. Lack of patients' motivation to practice exercise, time constraint and limited resources were the most frequently reported barriers to counseling. Further investigation on how to overcome such barriers is recommended.